(untitled) (Research, Society and Development, 2022)
Vaccination against HPV is an important prevention strategy that can reduce the burden of disease and the incidence of cancers in the long term. Therefore, this study aimed to characterize the temporal trend of HPV vaccine dose coverage and the variation in the level of material deprivation of Brazilian municipalities between 2012 and 2018. This is a longitudinal observational quantitative study that combined analysis of several observation units with a temporal trend design, which used data from the Sistema de Informação de Agravos de Notificação (SINAN). The frequencies of doses applied against the HPV vaccine were presented by year of analysis for the total population and stratified by sex. Municipalities were divided into quintiles according to the deprivation score of the Brazilian Deprivation Index. The frequencies of vaccine doses administered by deprivation quintiles were presented for the municipalities year by year. A total of 34,268,998 doses of HPV vaccine were applied in Brazil during the analyzed period, with higher doses during the national campaign period. Higher doses were observed among women compared to men (p=0.025). There was a trend of reduction in the number of doses over the years. Therefore, there is a need to develop measures to increase vaccination coverage against HPV, such as health education, sex education and public policies to reduce health and socioeconomic inequities.